A new genus and species, Barbaropus flatus, from Ecuador with notes on Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) - Xu, Ye; Qin, Dao-Zheng; Dietrich, Christopher H. (Zootaxa, 2019)
A new microleafhopper genus, Barbaropus gen. nov., is described based on a new species, Barbaropus flatus sp. nov. from Ecuador. Male habitus photos and illustrations of male genitalia are provided and differences between the new genus and closely related Neotropical genera are discussed. The relationship and the status of this new genus within the tribe are also discussed.